Long-term evaluation of a historical cohort of Iranian common variable immunodeficiency patients. (October 2014) - Aghamohammadi, Asghar; Abolhassani, Hassan; Latif, AmirHossein; Tabassomi, Firouzeh; Shokuhfar, Tahaamin; Torabi Sagvand, Babak; Shahinpour, Shervin; Mirminachi, Babak; Parvaneh, Nima; Movahedi, Masoud; Gharagozlou, Mohammad; Sherkat, Roya; et al.
<x xml:space="preserve">Abstract</x> Objectives: Common variable immune deficiency (CVID) is the most frequent form of symptomatic primary immunodeficiency disease, characterized by hypogammaglobulinemia, recurrent infections and increased predisposition to autoimmunity and malignancies. The aim of this study was to reconsider important points of previously performed studies on Iranian CVID patients diagnosed and followed from 1984 to 2013. Methods: Diagnosis was made using approved criteria including reductions of serum levels of immunoglobulins and exclusion of well-known single gene defects in individuals with an age >4 years and evidence of specific antibody deficiency. Results: Detailed information on demographic data, survival rates, clinical phenotypes, immunologic and genetic data and treatment of 173 patients are provided. The early onset presentation (74.5%) and rate of consanguineous marriage (61.2%) were considerably higher in our cohort. Our study revealed clinically related correlations regarding consanguinity, the population of naïve CD4+ T cells and switched-memory B cells, cytokine levels and special genetic factors (including HLA and AID genes). Conclusion: Despite current efforts, more comprehensive studies are needed, especially for classification and investigation of the genetic background and prognostic factors for patients with CVID in order to better managment and followup of patinets.